Politik Hukum Pembaharuan Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas (Kajian Pasal 74 beserta Penjelasannya) - Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2014)
The change of Corporate Social Responsibility (CSR) to be a legal obligation has made CSR become formality to fulfill certain obligations. The drafting process of the Constitution of Limited Company (UU PT), especially related to CSR regulations, has not fully reflected the characteristics of laws which are responsive in the middle of democratic political configuration. Therefore, this research focuses on discussing how the legal politics in the amendment of Consitution No 40 Year 2007 regarding Limited Company especially related to Article 74 which is about Corporate Social Responsibility and its explanations are. This was a normative legal research which was analyzed by using qualitative analysis. The findings show that the drafting process of UU PT has not fully reflected the characterstics of laws which are responsive in the middle of democratic political configuration. CSR regulations in UU PT, practically becoming the characteristics of Indonesian corporation laws, overlap with other existing laws.